Analysis of radio field requiment for RFID systems use in warehouses - Šeba, Jiří; Hruška, Roman; Švadlenka, Libor; Dobrodolac, Momčilo (My University, 2017)
RFID systems work on communication between data carriers and data readers. This basic data transmission is provided in virtual network, which have to be steady. Reading range of data readers is depending on many factors, as devices parameters, surroundings and type of data carrier.
Analýza požadavků na radiové pole pro RFID systémy používané ve skladech
Keywords: AIDC; RFID; Wi-Fi; AIDC; RFID; Wi-Fi